Test battery for measuring the perception and recognition of facial expressions of emotion - Wilhelm, Oliver; Hildebrandt, Andrea; Manske, Karsten; Schacht, Annekathrin; Sommer, Werner (Frontiers in Psychology, 2014)
Despite the importance of the perception and recognition of facial expressions in everyday life there is no comprehensive test battery for the multivariate assessment of these abilities. As a first step towards such a compilation, we present 16 tasks for measuring the perception and the recognition of emotional expressions, along with their difficulty and reliability. The scoring of these tasks focuses on either the speed or accuracy of performance. A sample of 269 healthy young adults completed all tasks. In general, accuracy and reaction time measures for overall emotion scores showed acceptable and high estimates of internal consistency and factor reliability. Deriving emotion-specific scores yielded reliabilities that were somewhat lower, yet mostly high enough to encourage studies of such measures. Analyses of task difficulty revealed that all tasks are suitable for measuring emotion perception- and recognition-related abilities in normal populations.